SUKUK SEBAGAI ALTERNATIF INSTRUMEN INVESTASI DAN PENDANAAN - Indriasari, Ika (Universitas Islam Negeri Sunan Kudus, 2014)
Sukuk is a form of Islamic investment instrument that is developing in Indonesia and various countries in the world. The superiority of Sukuk as a form of relatively safe investment makes sukuk accepted as an investment tool as well as funding for countries with a majority of Muslim and non-Muslim populations. The Indonesian government began to establish rules regarding sukuk since 2008 and continues to develop and innovate in sukuk transactions. Greetings and interest in investing in Indonesian sukuk are very good, both in the domestic and global markets. This can be seen from the oversubscription that occurs in Indonesian sukuk. Great interest in sukuk, especially in Indonesia shows that sukuk can provide good alternatives for investors and the country for funding needs in Indonesia's development.